Uji Aktivitas Tabir Surya dari Formula Emulgel yang Mengandung Nanokapsul Ekstrak Daun Ubi Jalar Ungu (Ipomoea batatas (L.)) Varietas Antin-3 - Dipahayu, Damaranie; Adenka, Daffa Sachio; Srianto, Jefri Ilyasa; Astutik, Novita Dwi (Jurnal Ilmiah Medicamento, 2025)
Flavonoids in purple sweet potato leaf extract (Ipomoea batatas (L.)) variety Antin-3 (Antin-3 extract) have properties as sunscreen. Flavonoids have a large molecular weight and easily decomposed by light, high temperature and external environmental. Modification of Antin-3 extract, namely nanoencapsulation with chitosan: NaTPP, is needed to reducing size and protect flavonoids so that they can remain in the skin layers longer to provide sunscreen protection. This study aims to formulate Antin-3 extract nanoencapsulation into emulgel sunscreen preparations and measure sunscreen activity through SPF, erythema and pigmentation values. The samples tested were base: Antin-3 nanoencapsulation of 0.3%: 0.6% and 0.9% = Base: F1: F2: F3. The results of the physical characteristics test of pH were respectively 6.39 ± 0.04: 5.98 ± 0.28: 5.62 ± 0.25: 5.3 ± 0.42 (sig 0.027 < 0.05) and the spreadability test were respectively 5.91 ± 0.17: 5.89 ± 0.15: 6.08 ± 0.31: 6.28 ± 0.16 (sig 0.266 > 0.05). For the SPF value respectively were 7.48 ± 0.01: 21.03 ± 0.03: 38.02 ± 0.10: 38.29 ± 0.07 (sig 0.00 < 0.05). Based samples has a weak protection, Antin-3 extract emulgel of 0.3% has a medium protection and Antin-3 extract emulgel of 0.6% and 0.9% have a high protection category. All of emulgel sunscreen has the ability to protect the skin from redness and pigmentation due to UV exposure.